Advanced competencies mapping of critical care nursing: a qualitative research in two Intensive Care Units - Alfieri, Emanuela; Mori, Marina; Barbui, Valentina; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2017)
Background and aim: Nowadays, in Italy, the nursing profession has suffered important changes in response to the needs of citizens’ health and to improve the quality of the health service in the country.  At the basis of this development there is an increase of the nurses’ knowledge, competencies and responsibilities. Currently, the presence of nurses who have followed post-basic training paths, and the subsequent acquisition of advanced clinical knowledge and specializations, has made it essential for the presence of competencies mappings for each specialty, also to differentiate them from general care nurses. The objective is to get a mapping of nurse’s individual competencies working in critical care, to analyze the context of the Parma Hospital and comparing it with the Lebanon Heart Hospital in Lebanon. Method: The survey has been done through a series of interviews involving some of the hospital staff, in order to collect opinions about the ICU nurses’ competencies. Results: What emerged from the data allowed us to get a list of important abilities, competencies, character traits and  intensive care nurse activities. Italians and Lebanese nurses appear to be prepared from a technical point of view, with a desire for improvement through specializations, masters and enabling courses in advanced health maneuvers. By respondents nurses can seize a strong desire for professional improvement. Conclusions: At the end of our research we were able to draw a list of different individual competencies, behavioral and moral characteristics. The nurse figure has a high potential and large professional improvement prospects, if more taken into account by the health system.